2021
DOI: 10.3390/diagnostics11081506
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Set of Spike and Receptor Binding Domain-Based Enzyme-Linked Immunosorbent Assays for SARS-CoV-2 Serological Testing

Abstract: The implementation and validation of anti-SARS-CoV-2 IgG serological assays are reported in this paper. S1 and RBD proteins were used to coat ELISA plates, and several secondary antibodies served as reporters. The assays were initially validated with 50 RT-PCR positive COVID-19 sera, which showed high IgG titers of mainly IgG1 isotype, followed by IgG3. Low or no IgG2 and IgG4 titers were detected. Then, the RBD/IgG assay was further validated with 887 serum samples from RT-PCR positive COVID-19 individuals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…IgG-A7 was subjected to an analytical platform of validated methodologies to assess its physicochemical profile for pharmaceutical developability and biological activity [ 17 , 18 , 19 ]. This platform considers determining protein content, purity, identity/integrity, and thermal stability.…”
Section: Methodsmentioning
confidence: 99%
“…IgG-A7 was subjected to an analytical platform of validated methodologies to assess its physicochemical profile for pharmaceutical developability and biological activity [ 17 , 18 , 19 ]. This platform considers determining protein content, purity, identity/integrity, and thermal stability.…”
Section: Methodsmentioning
confidence: 99%
“…Five out of the nine therapeutic antibodies except Etesevimab, Sotrovimab, Cilgavimab, and Tixagevimab are hIgG1 without Fc modifications. We [ 96 ] and other authors [ 97 ] have shown that IgG1 predominates the anti-SARS-CoV-2 immune response, followed by the IgG3 isotype. IgG2 and IgG4 are almost inexistent.…”
Section: Isotypes and Fc Engineeringmentioning
confidence: 90%
“…The expression, purification, and characterization of the RBD-WT and RBD-DT have been described elsewhere [ 27 ]. In brief, the plasmid containing the RBD-WT (or mutated in our laboratory to obtain the RBD-DT) donated by Dr Florian Kammer at Department of Microbiology, Icahn School of Medicine at Mount Sinai, New York, NY, USA.…”
Section: Methodsmentioning
confidence: 99%
“…This platform considers the determination of purity, identity/integrity, and thermal stability by analytical size exclusion chromatography (SEC), denaturing polyacrylamide electrophoresis (SDS-PAGE), and Protein Thermal Shift™ assay. All of these analytical techniques were performed using standard and well-known physicochemical methods for proteins [ 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%